Investigation on the status of professional identity of nursing staff in a Grade 3A Chinese medicine hospital (某三级甲等中医院护理人员职业认同感现状调查及相关性分析) - HONG Yanyan (洪艳燕); GUO Xiujun (郭秀君); LI Jian (李健); LIU Hui (刘翚); LIU Yuanyuan (刘园园) (中西医结合护理)
Objective To understand the present situation of professional identity of nursing staff in a Grade 3A Chinese medicine hospital, and to analyze the relevant factors. Methods A total of 705 nurses in a certain Grade 3A Chinese Medicine Hospital were selected to investigate the status of nurses' professional identity. Results The results indicated that the model's performance was appropriate with a cumulative interpretation rate of 85. 71% (＞80%). According to the investigation results, the average score of professional recognition of 705 nurses was (112. 238±22. 409), lower score were found associated with nurses' sense of self-determination and organizational influence, which were at the moderate level (≥4), and the rest were at the high level(＞5). The professional identity of nurses was positively correlated with their working years and professional titles (P＜0. 05)。. Conclusion To further improve the professional identity of nursing staff and strengthen the training of junior and junior nurses' sense of self-determination and organizational influence. (目的 了解三级甲等中医院护理人员的职业认同感现状并进行相关因素分析。方法 选择某三级甲等中医院705名护理人员进行护士职业认同感现状调查, 采用调查问卷的形式, 对临床护士实施一般资料及护士职业认同感问卷调查。结果 所选取的705名问卷样本为良好研究模型(累积解释率为85. 71%＞80. 00%)。问卷调查结果显示, 705名护理人员职业认同感平均得分(112. 238±22. 409)分, 各维度得分偏低的为护士自我决定感及组织影响感, 处于中等水平(≥4分), 其余均分属于高水平(＞5分)。护士的职业认同感与工作年限及职称呈正相关(P＜0. 05)。结论 应加强低年资及低职称护理人员自我决定感及组织影响感的培养, 进一步提高护理人员职业认同感)